(untitled) (Indian Journal of Animal Production and Management, 2014)
A study was carried out in Manipuri Pony, distributed in 3 valley districts of Manipur state. During the survey, 215 pony owners and farmers in 3 districts were interviewed about the various utility of the ponies and system of rearing practiced by them, using questionnaire. Regarding the utility pattern of the breed, 96.28% of the farmers were rearing Manipuri pony for Polo game and 3.72% kept these animals for both breeding and Polo. The pony farmers usually followed 3 (three) types of rearing practices. About 36.28% of pony owners’ followed extensive practice of rearing, under their broader supervision. Another, 36.28 % of the pony owners are rearing pony under partially intensive system (tethering) while 27.44% rears Pony under tethering system. It can be concluded that the pony owners are not earning any income from Pony rearing. Further, most of the time Pony wonder to the street and other crowded areas. In such state of management, the true genetic potential of the breed can’t be exploited. In view of this, immediate scientific intervention must be taken up for proper management of the breed in the long term perspective.